Congenital Cystic Lesion In Extra Hepatic Biliary Tract - Imran Ishaque; Durr -; Muhammad Kashif Nisar; Nadeem Baig; Obaidullah Khan; Naheed Gohar (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Objective:  To  illustrate congenital cystic lesions of the extra hepatic biliary tract on the idea of information of embryologic development through the magnetic resonance cholangiopancreatography (MRCP). Methods: Patients that were suspected to  have  been  suffering  from  biliary  disease  were  referred  to the MRI units, there the patients were narrowed done to confirm with the inclusion and exclusion cri-      teria, thereafter written and informed consent was obtained from them  and  the  procedure  was  ex-  plained to them in detail. MRCP was performed on a 1.5 Tesla  in MR unit, using phased-array coil for signal detection. Heavily T2 weighted images were  obtained  with  SSF-SE  technique.  The  axial  sec- tions were used for pancreatic and bile ducts whereas the coronal sections were used for the pancreatobiliary tract, axial and coronal source images and reformatted  images  were  evaluated  to-  gether for the possibility of any anomaly in extra hepatic biliary tract. This was an observational, cross sectional, prospective study with a  sample  size  of  377  patients.  Statistical  analysis  was  done  by  SPSS version 16. Results: Choledochal cyst was found in 11  of the 377 patients with a gender separate frequency of 6  out of 196 females and 5 out of 181 males, with a total frequency of 2.9% and a p-value at <0.001 which was significant. Conclusion: By identifying the inherent anomalies that  present  themselves  during  the  visualization  of the biliary tract through MRCP and MRI, while coupled with  information  regarding  the  clinical  signifi- cance of every entity, is vital for establishing an accurate diagnosis and in guiding acceptable clinical intervention and management.